Beyond the twee: Thuy's practical expression of living the Mercy Education Value of hospitality. Issue 2 (3rd May 2016) - Hyde, Brendan
Abstract: This article utilises hermeneutic phenomenology as a theoretical framework for reflecting upon and interpreting the Mercy Education Value of hospitality. It describes an incident involving the author's encounter with a member of staff upon his new appointment in a Catholic secondary college formed in the Mercy Tradition. Through this article, the possibilities opened by such an encounter for hermeneutic phenomenology are explored using van Manen's lifeworld existentials as guides to reflection upon the described incident. The four lifeworld existentials are lived space (spatiality), lived body (corporeality), lived time (temporality) and lived other (relationality). In using these as guides to reflection, it is argued that some insights into the Mercy value of hospitality may be gleaned, namely that to be Mercy involves: (1) exceeding the carefully and socially programmed how are you – fine exchange; (2) an encounter with the other – the stranger – in whom is to be found the person of Jesus Christ, in which both participants are transformed; and (3) taking a risk – pushing boundaries so as to enter into relationship with the other.